New psychoactive substances as part of polydrug abuse within opioid maintenance treatment revealed by comprehensive high‐resolution mass spectrometric urine drug screening. (13th January 2016) - Heikman, Pertti; Sundström, Mira; Pelander, Anna; Ojanperä, Ilkka
Abstract : Objective: At present, polydrug abuse comprises, besides traditional illicit drugs, new psychoactive substances (NPS) and non‐prescribed psychotropic medicines (N‐PPM). Polydrug abuse was comprehensively evaluated among opioid‐dependent patients undergoing opioid maintenance treatment (OMT). Methods: Two hundred consecutively collected urine samples from 82 OMT patients (52 male) treated with methadone or buprenorphine‐naloxone medication were studied using a liquid chromatography/time‐of‐flight mass spectrometry screening method. The method enables simultaneous detection of hundreds of abused substances covering the traditional drugs of abuse and many NPS as well as N‐PPM. Results: Ninety‐two (45.8%) samples were positive for the abused substances. Benzodiazepines (29.0%), amphetamines (19.5%), cannabinoids (17.0%), NPS (13.0%), N‐PPM (9.0%), and opioids (9.0%) were detected in different combinations. The simultaneous occurrence of up to three groups of abused substances was common (40.0%), and in one sample, all six groups were found. The stimulant NPS alpha ‐pyrrolidinovalerophenone was found in 10.0% and the sedative N‐PPM pregabalin in 4.0% of the samples. The patients were seldom aware of what particular NPS they had abused. Conclusions: A widespread occurrence of abused substances beyond the ordinary was revealed. Identifying these patients is essential as polydrug abuse is a safety risk to the patient and may cause attrition from OMT. Copyright © 2016 John Wiley & Sons, Ltd.